Quanto vale a educação básica? O mercado educacional no contexto da BNCC - Carvalho, Bia (2024)
This research focuses on the role of the educational market in developing and implementing the National Common Curricular Base (BNCC) (Brazil, 2017), adopting as reference the Kroton/Cogna group basic education branch, Somos Educação. The research analyzes the Kroton/Cogna group's strategic shifts regarding its role in basic education in the context of the BNCC approval. To do so, we conducted qualitative and quantitative research. The initial step was the bibliographic review with the CAPES Theses and Dissertations Bank and the Scielo platform as primary sources. We reviewed papers whose analysis overlapped with our research objectives and studies that, although not fully aligned with our focus, provided compelling insights into complementary areas such as the BNCC content and context and the current context of educational policies. We pursued archival research focused on reviewing the quarterly results releases the Kroton/Cogna group presented to its investors between 2015 and 2021. This research process allowed us to retrieve the history of New Public Management and observe the direct impact this management style had on education, both in terms of public policies through the BNCC and in the relationship with the private sector. The research presents the BNCC development process, drawing attention to the significant role private institutions played in it. The in-depth analysis of Kroton/Cogna's operations, including its history and products, demonstrates the company's extensive reach in basic education. The research could also demonstrate that the company's priority shift from higher to basic education occurred concomitantly with the BNCC approval process. Even though it is not possible to state categorically a causal relationship between these two phenomena, the research brings to light evidence that these shifts stemmed from a short-term interest – related to market expansion through the redevelopment of teaching materials and the content creation targeting standardized tests – and a long-term interest – directed at training the workforce training according to a specific worldview.